THE CONTRIBUTION OF GRIP STRENGTH AND EYE-HAND COORDINATION TOWARDS SERVICE ACCURACY IN TENNIS ATHLETES - Yogi Andria; Andre Igoresky (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
The problem in this study is that the achievements of KTC tennis athletes have not been very good. This achievement is not yet so well due to many factors, but based on observations and interviews with club coaches the most dominant factor is the low service accuracy of KTC Pariaman athletes. For this reason, it is necessary to conduct a study with the aim to find out whether there is the Contribution of grip strength and eye-hand coordination to the accuracy of service in the City Pariaman Tennis Club (KTC) tennis athletes. This type of research is correlational. The study population was all KTC Pariaman tennis athletes, amounting to 32 people. Sampling in this study was carried out by purposive sampling technique, amounting to 20 people. Data was collected using a test of all three variables. Grip strength variable data is taken using a test tool called the Handgrip Dynamometer, hand eye coordination variable using the Ballwerfen Und-fangen test and service accuracy using the Hewitt tennis achievement test. Data analysis techniques are product-moment correlation, and multiple correlation. The results of the data analysis show that: 1) The strength of grip provides a significant contribution to the accuracy of he service of KTC Pariaman tennis athletes, with a contribution of 23.5%, 2) Eye-hand coordination provides a significant contribution to the accuracy of the service of KTC Pariaman tennis athletes, with contributions 25.3%, 3). The strength of grip and eye-hand coordination both contributed significantly to the accuracy of the service of KTC Pariaman tennis athletes, with a contribution of 33.1%.